A Survey of the Thickness of the Shoe Sole among Junior High School Students in Greater Jakarta for Shoe Correction in Seat Height-Popliteal Height Equation - ., Yanto (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
This paper aimed to present a survey result of the thickness of the shoe sole among junior high school students in Greater Jakarta, Indonesia. A number of 160 samples of the shoe wearing by junior high school students (85 boys and 65 girls) from Grade 7-Grade 9 was measured. The thickness of the sole of the shoe wearing by them were measured. The results were presented in mean and SD for each grade and gender. T-test results showed that no significant differences were found for thickness of the sole of the shoe wearing by boys and girls within the same grade. Anova test results also revealed that no significant differences were found for thickness of the sole of the shoe among boys in Grade 7-9 (F=0.54, p=0.58) and girls (F=1.06, p=0.35). Findings in this study revealed that a 20mm shoe correction, as often used by many researchers, which is added to the popliteal height to dimension the seat height (SH) is appropriate to be used for population under study. The results of this study provided sufficient justification for the use of a 2 cm shoe correction (SC) in addition to popliteal height when determining seat height of the chair.